High multiple carriage and emergence of Streptococcus pneumoniae vaccine serotype variants in Malawian children - Kamng’ona, Arox W. (BMC Infect Dis, 2015)
BACKGROUND: Carriage of either single or multiple pneumococcal serotypes (multiple carriage) is a prerequisite for developing invasive pneumococcal disease. However, despite the reported high rates of pneumococcal carriage in Malawi, no data on carriage of multiple serotypes has been reported previously. Our study provides the first description of the prevalence of multiple pneumococcal carriage in Malawi. METHODS: The study was conducted in Blantyre and Karonga districts in Malawi, from 2008 to 2012. We recruited 116 children aged 0–13 years. These children were either HIV-infected (N = 44) or uninfected (N = 72). Nasopharyngeal samples were collected using sterile swabs. Pneumococcal serotypes in the samples were identified by microarray. Strains that could not be typed by microarray were sequenced to characterise possible genetic alterations within the capsular polysaccharide (CPS) locus. RESULTS: The microarray identified 179 pneumococcal strains (from 116 subjects), encompassing 43 distinct serotypes and non-typeable (NT) strains. Forty per cent (46/116) of children carried multiple serotypes. Carriage of vaccine type (VT) strains was higher (p = 0.028) in younger (0–2 years) children (71 %, 40/56) compared to older (3–13 years) children (50 %, 30/60). Genetic variations within the CPS locus of known serotypes were observed in 19 % (34/179) of the strains identified. The variants included 13-valent pneumococcal conjugate vaccine (PCV13) serotypes 6B and 19A, and the polysaccharide vaccine serotype 20. Serotype 6B variants were the most frequently isolated (47 %, 16/34). Unlike the wild type, the CPS locus of the 6B variants contained an insertion of the licD-family phosphotransferase gene. The CPS locus of 19A- and 20-variants contained an inversion in the sugar-biosynthesis (rmlD) gene and a 717 bp deletion within the transferase (whaF) gene, respectively. CONCLUSIONS: The high multiple carriage in Malawian children provides opportunities for genetic exchange through horizontal gene transfer. This may potentially lead to CPS locus variants and vaccine escape. Variants reported here occurred naturally, however, PCV13 introduction could exacerbate the CPS genetic variations. Further studies are therefore recommended to assess the invasive potential of these variants and establish whether PCV13 would offer cross-protection. We have shown that younger children (0–2 years) are a reservoir of VT serotypes, which makes them an ideal target for vaccination.